Fitness Level in Mojo VI Surabaya Elementary School Students - Nabilah Ishanan Ramadhan; Hening Laswati; Kristanti Wanito Wigati; Sri Mardjiati Mei Wulan (Faculty of Medicine, Universitas Airlangga, 2023)
Background: A sedentary lifestyle such as watching TV and video for a long time, or playing PlayStation, is experienced by two-thirds of children, especially in developing countries. The fitness levels of elementary school students are not all in a good condition. So far, there is no study of healthy children with 2-minute walk test method. Therefore, the researcher is interested to do research about fitness level with 2-minute walk test. Aim: The purpose of this research is to determine the fitness level of Mojo VI elementary school Surabaya. Material and Methods: The method used in this research is descriptive observational with a cross-sectional research design using total sampling. Data collection was using primary data obtained from the results of 2-minute walk test. Results: The fitness level based on age obtained the highest average value at the oldest age of 12 years old with an average of 207.30 m±17.359. While the lowest average value at the youngest age was 184.96 m±15.991. Meanwhile, based on gender, it obtained higher average value in male students (201.81 m±22.06 m) than female students (194.30 m±14.29 m). Conclusion: The higher the age, the higher the student's fitness level. Meanwhile, based on gender, the fitness level of a male is higher than a woman.